Exploring the potential of bioactive compounds of Capparis spinosa L. from Morocco: Unveiling its antioxidant and antifungal powers against Alternaria alternata - Chiboub, Basma; Maatougui, Abdesselam; Aboukhalid, Kaoutar; Khallou, Abdelhak; Khallouf, Hanane; Nazih, Abderrahmane; Esseghir, Loubna; Baghour, Mourad (Plant Science Today, 2024)
Capparis spinosa L. is a Mediterranean shrub and one of the most important species of the gender Capparis due to its ecological, medicinal and economic importance. This species has strong adaptation characteristics to regions with fluctuating climates. This work aims to evaluate the effect of the locality’s climate and plant’s parts on the content of polyphenols, flavonoids and antioxidant and antifungal activities of caper leaves and seeds. The present study was carried out in 7 localities in 2 Moroccan regions, Oriental and Fez-Meknes, where we collected leaves and seeds samples. Phenolic compounds were determined by the Folin Ciocalteu method, antioxidant activity was studied by DPPH and ABTS tests and an in vitro test of antifungal activity was achieved using Alternaria alternata. The analysis of variance showed no significant effect of locality, plant’s parts and their interaction on the phenolic compounds, antioxidant and antifungal activities of C. spinosa. Methanolic leaves extracts demonstrated the most favorable outcomes, yielding a maximum polyphenol content of 124.48 ± 0.05 mg EAG/g DW. Additionally, the maximum flavonoid content was recorded at 24.51 ± 0.01 mg EQ/g DW. The evaluation of the antioxidant activity showed that the minimum inhibitory concentration at 50 % (IC50) is 2.06 ± 0.05 mg/mL and 2.05 ± 0.02 mg/mL using DPPH and ABTS tests respectively. These extracts exhibited the highest % of inhibition, 30.59 % at 1000 ppm against A. alternata. The richness of the caper plant in bioactive compounds reveals an interest in its therapeutic and pharmaceutical virtues. In addition, it could be an alternative to chemicals for the control of phytopathogenic fungi on fruits or vegetables.